Penerapan akuntansi aset biologis berdasarkan PSAK No. 69 pada PT Astra Agro Lestari Tbk - Marcella, Jenny; Saerang, David Paul Elia; Pinatik, Sherly (Yayasan Widyantara Nawasena Raharja, 2024)
In the agribusiness industry, biological assets emerge as the most crucial assets with significant value. Within this sector, PT Astra Agro Lestari Tbk stands out as a company engaged in various activities, including palm oil plantation. Palm oil serves as a biological asset managed by PT Astra Agro Lestari Tbk, encompassing recognition, measurement, and disclosure aspects. This research aims to examine the implementation of biological asset accounting in accordance with PSAK No. 69 at PT Astra Agro Lestari Tbk. Employing a qualitative research approach rooted in postpositivism philosophy, the study investigates natural phenomena or events. The finding reveal that PT Astra Agro Lestari Tbk adheres to the provisions outlined in PSAK No. 69 concerning the recognition, measurement, and disclosure of biological assets. The company exercises control over biological assets through activities such as planting, maintenance, and upkeep of oil palm trees over time. Biological assets are measured based on fair value less costs to sell. Moreover, PT Astra Agro Lestari Tbk discloses gains and losses incurred during the reporting period in the profit and loss statement, while distinguishing between producing and non-producing plants.